Lethal and sublethal toxicity assessment of Bacillus thuringiensis var. israelensis and Beauveria bassiana based bioinsecticides to the aquatic insect Chironomus riparius - Bordalo, Maria D. (2019)
Despite being considered environmentally safe, a deeper environmental risk assessment is needed for microbial insecticides; special attention should be devoted to their sublethal toxicity to non-target species. This study evaluated effects of VectoBac® 12AS - VB (based on the bacterium Bacillus thurigiensis var. israelensis) and Naturalis®-L - NL (based on the fungus Beauveria bassiana) on the aquatic insect Chironomus riparius life- history and biochemical responses. Acute tests estimated a 48 h-LC50 (median lethal concentration) of 1.85 μg/L (VB) and 34.7 mg/L (NL). Under sub- lethal exposure, VB decreased adults' emergence (LOEC – lowest observed effect concentration of 80 ng/L) while NL impaired larval growth (LOEC of 0.32 mg/L) and delayed emergence (LOEC of 2 mg/L for males and 0.8 mg/L for females). Despite not being monotonic, phenoloxidase activity increased (LOEC of 20 ng/L (VB) and 2 mg/L (NL)), suggesting activation of the immune system. There were no indications of oxidative damage nor neurotox- icity. Catalase activity was stimulated with all VB treatments, possibly associated with detoxification of immune response products. Under NL exposure, glutathione-S-transferase activity increased but did not show a dose- dependent response and, total glutathione decreased in the highest concentration. Exposure to both formulations caused the increase in protein content, while carbohydrate and lipids were not altered. This study revealed the susceptibility of C. riparius to VB and NL at concentrations below the ones recommended for field application, with potential population-level effects. These results add important information for the risk assessment of these microbial insecticides in aquatic ecosystems, considering relevant sublethal endpoints and raising concern about the adverse effects on non-target aquatic organisms.